Perspectives on Cognitive Therapy Training within Community Mental Health Settings: Implications for Clinician Satisfaction and Skill Development. (29th September 2012) - Wiltsey Stirman, Shannon; Miller, Christopher J.; Toder, Katherine; Calloway, Amber; Beck, Aaron T.; Evans, Arthur C.; Crits-Christoph, Paul
Abstract : Despite the mounting evidence of the benefits of cognitive therapy for depression and suicidal behaviors over usual care, like other evidence-based psychosocial treatments (EBTs), it has not been widely adopted in clinical practice. Studies have shown that training followed by intensive consultation is needed to prepare providers to an appropriate level of competency in complex, multisession treatment packages such as cognitive therapy. Given the critical role of training in EBT implementation, more information on factors associated with the success and challenges of training programs is needed. To identify potential reasons for variation in training outcomes across ten agencies in a large, urban community mental health system, we explored program evaluation data and examined provider, consultant, and training program administrator perspectives through follow-up interviews. Perceptions of cognitive therapy, contextual factors, and reactions to feedback on audio recordings emerged as broad categories of themes identified from interviews. These factors may interact and impact clinician efforts to learn cognitive therapy and deliver it skillfully in their practice. The findings highlight experiences and stakeholder perspectives that may contribute to more or less successful training outcomes.